ACCOUNTABILITY ANALYSIS IN MANAGEMENT OF VILLAGE FUNDS (DD) IN PAKUKU JAYA VILLAGE, TOMINI SUB-DISTRICT, BOLAANG MONGONDOW SELATAN DISTRICT - juliaty daaliwa; ELY IBRAHIM; Siske Anani (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This internship was carried out with the aim of knowing and analyzing accountability in managing village funds (DD) in Pakuku Jaya Village, Tomini District, South Bolaanag Mongondow Regency Report method used is qualitative research using data collection techniques carried out using observation techniques, interviews and documents. The author shows the Accountability Analysis in Village Fund Management (DD) in Pakuku Jaya Village, Tomini District, South Bolaang Mongondow Regency. Village Fund Management Analysis Is A Very Important Thing Because In The Implementation Of The Village Fund Management There Is A Process Of Planning, Implementation, Administration, Reporting, And Accountability.